Efektivitas Peningkatan Kemampuan Mengingat Kosakata Gairaigo Menggunakan Media Kartu Kwartet (pada Siswa Kelas X SMK Mandala Tiara Bangsa 2019/2020) - Meliana, Igat (Journal of Japanese Language Education and Linguistics, 2020)
The quartet card learning is a game card and consists of colorful images and vocabulary. It belongs to teaching tools for the whole learning. In the learning process, all students can apply it. Therefore, the visibility of students is not limited to using imagery media only. The color of the Gairaigo letter can also reinforce students to memorize the Gairaigo vocabulary.Furthermore, due to the attractive card design, the game can also increase the motivation of students in learning the Gairaigo vocabulary. The purpose of this research is to determine the effectiveness of the use of Learning Media, quartet card, on the ability to remember Gairaigo vocabulary. The research method used was the quantitative method of authentic experimental design, with the sample of the students of SMK Mandala Tiara Bangsa, divided into control and experimentation classes. It showed that learning by using the media of the Quartet card learning was practical. It could increase the value of learning outcomes of Gairaigo vocabulary and attract students' interest and attention in learning Japanese. Hence, it also gave an active learning experience in the classroom.